Oceanographic chaos and its role in larval self-recruitment and connectivity among fish populations in Micronesia. (30th September 2021) - Wolanski, Eric; Richmond, Robert H.; Golbuu, Yimnang
Abstract: A 30-year time series of the recruitment of rabbit fish, a herbivorous coral reef fish, on the island of Guam in the tropical western Pacific, showed variability that ENSO alone does not explain. To help explain this variability, a high-resolution biophysical model that includes directional swimming reveals how mesoscale turbulence and ENSO-driven changes in the ocean circulation control the self-recruitment of rabbit fish. ENSO drives island wakes that enhance the capacity to retain locally spawned larvae, and mesoscale turbulence generates much variability and promotes seaward dispersion at time scales larger than the Pelagic Larval Duration. The same processes are predicted to occur for the self-recruitment of grouper fish, a carnivorous coral reef fish, in Palau, Micronesia. The models suggests that 99% of these fish larvae are exported seaward from Guam and Palau. Those larvae are the ones that could provide connectivity between reefs and islands in Micronesia. This connectivity for the grouper fish was predicted using an altimetry-driven advection-diffusion oceanography model for 40 mass spawning events spread over 10 years. The mesoscale turbulence, and not the mean oceanographic currents, is the dominant process controlling the connectivity, which is thus chaotic. This finding applies also in the Galapagos archipelago and the Coral Sea fringing the Great Barrier Reef. Graphical abstract: Image 1 Highlights: Intense meso-scale turbulence and the El Nino-La Nina phenomenon dominate the near-surface water circulation in Micronesia. The self-recruitment and the connectivity of reef fish in Micronesia is chaotic. Similar chaos also occurs in other archipelagos in the world.